Automatic Exchange of Information and Developing Country Capacity: The Indonesian Experience (Indonesian Tax Justice Review, 2024)
Automatic Exchange of Information has become a cornerstone of global tax transparency initiatives aimed at combating offshore tax evasion. This paper evaluates Indonesia’s implementation of AEOI from a capacity and tax justice perspective. Using institutional analysis, the study assesses legal preparedness, data utilization, and enforcement outcomes. The findings indicate that although AEOI enhances access to offshore financial information, limited analytical capacity and resource constraints reduce its practical effectiveness. The paper argues that transparency alone does not guarantee tax justice without the ability to translate information into enforcement actions. The global contribution of this study lies in highlighting capacity asymmetries embedded in international transparency regimes. Indonesia’s experience demonstrates that developing countries require sustained technical assistance and institutional investment to benefit fully from global information exchange. The study contributes to international tax scholarship by reframing transparency as a justice issue rather than a purely technical reform.